Impact of Cochlear Dose on Hearing Preservation following Stereotactic Radiosurgery and Fractionated Stereotactic Radiotherapy for the Treatment of Vestibular Schwannoma - Chung, Lawrance K.; Ung, Nolan; Sheppard, John P.; Nguyen, Thien; Lagman, Carlito; Choy, Winward; Tenn, Stephen; Pouratian, Nader; Lee, Percy; Kaprealian, Tania; Selch, Michael; De Salles, Antonio; Gopen, Quinton; Yang, Isaac (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective The objective of this study was to examine the effect of cochlear dose on hearing preservation in stereotactic radiosurgery (SRS) and fractionated stereotactic radiotherapy (fSRT) for vestibular schwannoma (VS).Design This is a retrospective case–control study.Setting This study was completed at the Ronald Reagan UCLA Medical Center, a university-affiliated tertiary care center.Participants Patients who underwent SRS (marginal dose of 12 Gy) or fSRT (marginal dose of 50.4 Gy) procedures for VS were included in the study.Main Outcome Measures The main outcome measure was hearing preservation. Audiometric data, when available, were used to determine the level of hearing according to the Gardner Robertson scale.Results A total of 38 patients (14 SRS and 24 fSRT) were analyzed. SRS patients with decreased hearing received a significantly higher minimum cochlear dose (7.41 vs. 4.24 Gy, p = 0.02) as compared with those with stable hearing. In fSRT patients, there were no significant differences in cochlear dose for patients with decreased hearing as compared with those with stable hearing. For SRS patients, who received a minimum cochlear dose above 6 Gy, there was a significant risk of decreased hearing preservation (odds ratio: 32, p = 0.02).Conclusion Higher minimum cochlear dose was predictive of decreased hearing preservation following SRS. Though the study is low powered, the radiation dose to the cochlea should be a parameter that is considered when planning SRS or fSRT therapies for patients with VS.
Keywords: cochlear dose; hearing; stereotactic radiosurgery; fractionated stereotactic radiotherapy; vestibular schwannoma